Impact of Employee Loyalty on Employee Performance: Empirical Evidence from Chinese Pharmaceutical Industry - Ma, Yuning; Swatdikun, Trairong; Salamolee, Alisara; Prempanichnukul, Varaporn (Science, Technology, and Social Sciences Procedia, 2022)
This research takes the pharmaceutical enterprises in Henan Province as the research to explore employee and examine the impact employee loyalty on employee performance as the research method for the relationship between employee loyalty and employee work performance. A questionnaire, using descriptive statistics, multiple regression analysis, and the main indicator that: Employee behavior loyalty has a significant positive promotion effect on employee performance. Employee attitude and loyalty has a significant positive effect on employee performance. The comprehensive loyalty of employees has a significant positive effect on employee performance.